"Impacto de las reformas tributarias sobre los impuestos indirectos en la empresa "Comercial Karinita", del cantón Quevedo, 2012." - Anzules Vinces, Otto Roberto (2013)
Analysis of the Impact of Tax Reforms on indirect taxation in the business "Commercial Karinita" was held in Guangzhou Quevedo, Los Rios Province, Ecuador, in 2012. The main objective of the research was measuring the economic impact of tax reforms, especially indirect taxes on the retail price (RRP) of the products of "Commercial Karinita" Quevedo town, during the second half of 2012, compared to the first half of the same year. The conclusions are summarized as follows: The sales prices of the line items "Furniture" of Commercial Karinita, increased 12% for domestic and 35% for imports, during the second half of 2012, compared to the first half of the year, selling prices of the line items "White and Brown" increased 12% for domestic and 35% for imports, in the products offered by "Commercial Karinita" during the second half of 2012, compared with the first half of the year. The implementation of the tax reforms of 2009 and 2011, during the second half of 2012, in Commercial Karinita, generated an economic impact that produced the decline in demand White lines items, Coffee & Furniture, negative variations ranging about 49,5, the general hypothesis posed: "The study applied to the current tax reform will determine the level of economic impact (%) suffered the company "Commercial Karinita" Quevedo Canton, during the second half of 2012 ", is fully tested. The main recommendations were: Ensure that the customer "see" the price increase of the line "furniture" of Commercial Karinita, concealed behind a promotion, gift or sales strategy for recovering market volumes above; Distribute "weight" of the increase in the selling prices of the line items "White and Brown" among the least sensitive products (domestic, lower price, etc..) Ensure the purchase, if possible, domestic goods and while designing a marketing plan in order to overcome the negative change in demand